2009
DOI: 10.1200/jco.2008.19.4225
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Mastectomy Rates at the Mayo Clinic Rochester: Effect of Surgical Year and Preoperative Magnetic Resonance Imaging

Abstract: A B S T R A C T PurposeRecent changes have occurred in the presurgical planning for breast cancer, including the introduction of preoperative breast magnetic resonance imaging (MRI). We sought to analyze the trends in mastectomy rates and the relationship to preoperative MRI and surgical year at Mayo Clinic, Rochester, MN. Patients and MethodsWe identified 5,405 patients who underwent surgery between 1997 and 2006. Patients undergoing MRI were identified from a prospective database. Trends in mastectomy rate a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
222
6
6

Year Published

2009
2009
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 343 publications
(245 citation statements)
references
References 41 publications
11
222
6
6
Order By: Relevance
“…Mastectomy rates did not vary by diagnostic year in the present study. This is in contrast to results from U.S. SEER data that indicate a continuing decline in mastectomy rates from 2000 but with the possibility of an upturn during 2005(Fisher et al, 1995Tuttle et al, 2007;Katipamula et al, 2009;Dragun et al, 2012a;2012b). This was supported by some regional and institutional data from the U.S. and evidently was influenced by an upturn in contra-lateral prophylactic mastectomies (Tuttle et al, 2007;Katipamula et al, 2009;Dragun et al, 2012a;2012b).…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…Mastectomy rates did not vary by diagnostic year in the present study. This is in contrast to results from U.S. SEER data that indicate a continuing decline in mastectomy rates from 2000 but with the possibility of an upturn during 2005(Fisher et al, 1995Tuttle et al, 2007;Katipamula et al, 2009;Dragun et al, 2012a;2012b). This was supported by some regional and institutional data from the U.S. and evidently was influenced by an upturn in contra-lateral prophylactic mastectomies (Tuttle et al, 2007;Katipamula et al, 2009;Dragun et al, 2012a;2012b).…”
Section: Discussioncontrasting
confidence: 60%
“…Statement and reviews of evidence from randomized trials (Abrams et al, 1995;Fisher et al, 1995), mastectomy rates declined markedly in the U.S. (Lazovich et al, 1991;Lazovich et al, 1997;Habermann et al, 2010), Canada, (Gaudette et al, 2004) European countries, (Zorzi et al, 2006), although with a more recent upturn suggested in some North American localities (Tuttle et al, 2007;Katipamula et al, 2009;Dragun et al, 2012a;2012b). Australian data also showed a trend away from mastectomy towards breast conserving surgery both nationally and in a number of jurisdictions (Hill et al, 1990;1994;Byrne et al, 1993;South Australian Cancer Registry, 2000;Cuncins-Hearn et al, 2006;Kricker, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, some studies conducted in single institutions using hospital-based records showed an increasing trend in mastectomies [22][23][24] . The justification of this increase was related to the use of MRI of the breast 23 and greater liberality in conducting prophylactic operations 25 .…”
Section: Discussion Discussion Discussion Discussionmentioning
confidence: 99%
“…The justification of this increase was related to the use of MRI of the breast 23 and greater liberality in conducting prophylactic operations 25 . Studies using population-based cancer registries showed reduction of mastectomies in the United States 25 , Norway 26 and Spain 27 , though.…”
Section: Discussion Discussion Discussion Discussionmentioning
confidence: 99%
“…15 After this consensus had been published, mastectomy rates decreased to less than 50% in some countries. [16][17][18][19][20][21][22] Recently, some American hospitals have reported an increase in mastectomy rates, although American and European statistics in general do not show this increase. [16][17][18][19][20][21][22][23][24][25] We have not found any studies in major databases (PubMed or SciELO) comparing the rates of different types of surgery for breast cancer in Brazilian public institutions.…”
Section: Introductionmentioning
confidence: 99%